Translating for Young Minds: Techniques to Ensure Accuracy and Acceptability in Children’s Bible Stories - Herianto; Mangatur Rudolf Nababan; Riyadi Santosa (Script Journal: Journal of Linguistics and English Teaching, 2025)
Background: Children’s literature, particularly bible stories, plays a crucial role in shaping children’s moral values. However, translation quality in children’s bible stories is often overlooked, impacting accuracy and acceptability. This study examines the translation techniques used in Classic Children’s Bible, assessing their influence on translation quality, particularly accuracy and acceptability.Methodology: This descriptive qualitative study is product-oriented research which was focused on 43 children’s Bible stories. Data were collected from Classic Children’s Bible and its Indonesian translation. They were analyzed through content analysis, taxonomy analysis, componential analysis, and cultural theme analysis.Findings: The study found that some techniques influence translation quality in terms of accuracy and acceptability. The mostly used techniques (established equivalence, transposition, and modulation) contribute to accuracy and acceptability. In addition, it also found the translator’s effort in maintaining the original story through correction technique. However, accuracy and acceptability are considered to gain a nearly perfect score because of several techniques (discursive creation and deletion).Conclusion: This study confirms the crucial role of translation techniques in ensuring accuracy and acceptability in children’s Bible story translations. Translation techniques such as established equivalence, transposition, and modulation were effective while discursive creation, deletion, and reduction reduced accuracy.Originality: The translation of children’s Bible stories has been studied primarily in terms of methods, techniques, and quality. Howeverseveral studies examined some linguistic parts, not the whole story. In filling the gap, this study investigated the translation techniques in 43 children’s Bible story translations as the whole story.